Implementasi Proses Peradilan Melalui E-Court dalam Penyelesaian Perkara Perdata di Pengadilan Negeri Kefamenanu Kelas II - Benediktha Marice Leltakaeb; Simplexius Asa; A. Resopijani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The digital change in Indonesia's court system has led to the use of electronic court services, known as e-court, to make the legal process more efficient, open, and easier to access. This study looks at two main questions: (1) how the e-court system is used to handle civil cases at the Kefamenanu District Court Class II, and (2) what difficulties come up during its use. The goal of this research is to check how well e-court is working and to find out both technical and non-technical problems faced by the court and the people using it. The research uses a legal method that combines looking at laws with real data collected from the field. Information was gathered directly through conversations with judges, court workers, lawyers, and people who use the courts. Other information came from books and legal rules. The data was studied using a method that describes what is found in detail. The results show that the e-court system at the Kefamenanu District Court Class II is mostly being used as it should, following the Supreme Court's rules from 2022, and helps make the court system simpler, faster, and cheaper. However, there are still some problems, like poor internet connections, system issues, and not enough knowledge of digital tools among the public. These results show that even though e-court makes handling civil cases more efficient, there is still a need to improve the system and help people better understand how to use it.